Theileria parva: In vitro studies on the effects of holding temperature, PH and medium on sporozoite infectivity - Kimbita, E.N.; Silayo, R.S.; Dolan, T.T. (Springer, 2004)
The effects of holding temperature, pH and medium on the infectivity of Theileria parva sporozoites were investigated using an in vitro infectivity assay. The sporozoite infectivity lasted for 72 h at a holding temperature of 4 C but for only 24 h at 24 degrees C. Sporozoite infectivity was found to be sensitive to pH variations and sporozoites were most infective between pH 7 and pH 8. There was a significant loss in infectivity at pH 5 and infectivity was almost totally abolished at pH 9. Theileria parva sporozoites are usually held and manipulated in Eagle's minimum essential medium (MEM) with Earles' salts. In this study. Leibovitz-15 supplemented with 15% fetal bovine serum gave a significantly better infectivity than Eagle's MEM (3.8 log units versus 1.0 log units) or any other medium. The importance of proper management of the T. parva sporozoite environment in the laboratory or field is emphasized by the findings in these studies and might also explain some of the failures of vaccination when the pH of the holding medium was allowed to deteriorate.